2017
DOI: 10.1093/ejcts/ezx065
|View full text |Cite
|
Sign up to set email alerts
|

Genetic abnormalities in bicuspid aortic valve root phenotype: preliminary results†

Abstract: Our preliminary study demonstrates a high prevalence and a wide spectrum of rare genetic variants in patients with the BAV root phenotype, indicative of the potentially congenital origin of associated aortopathy in this specific BAV cohort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 23 publications
1
41
0
Order By: Relevance
“…In accordance to these findings, subsequent studies showed that the prevalence of NOTCH1 missense variants was in the range of 10%-18% in BAV patients with concomitant ascending aortic aneurysms (see Table 1) [10][11][12]. These potentially deleterious NOTCH1 variants were mostly absent in the tricuspid aortic valve (TAV) control groups without aortopathy.…”
Section: Genetic Signaling Pathways and Bicuspid Aortopathymentioning
confidence: 62%
“…In accordance to these findings, subsequent studies showed that the prevalence of NOTCH1 missense variants was in the range of 10%-18% in BAV patients with concomitant ascending aortic aneurysms (see Table 1) [10][11][12]. These potentially deleterious NOTCH1 variants were mostly absent in the tricuspid aortic valve (TAV) control groups without aortopathy.…”
Section: Genetic Signaling Pathways and Bicuspid Aortopathymentioning
confidence: 62%
“…This bicuspid aortic valve subtype lacks other clinical features of the Marfan syndrome, but it shares some of its pathogenic and genetic features. Such aortic phenotypes have been described for decades in conjunction with, but also independently of their etiology, as 'annuloaortic ectasia' [24], or as 'forme fruste' of Marfan syndrome [25], Today, this bicuspid aortic phenotype has been associated with nucleotide sequence variants in the FBN1 gene [26,27], but also with other genes known to cause genetic aortic diseases [27].…”
Section: Aortic Valve Diseasementioning
confidence: 99%
“…21 This initial report was followed by many others, describing an association between variations in NOTCH1 and BAV, BAV/TAA, hypoplastic left heart syndrome (HLHS), aortic valve stenosis, and coarctation. [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] Most of the identified variants in these reports are missense variants, In 2016, a large scale screening of 428 probands with left-sided CHD (LS-CHD), confined to aortic valve stenosis, BAV, coarctation of the aorta, and HLHS, revealed the presence of 14 NOTCH1 mutations, including splicing mutations, truncating mutations and a whole gene deletion ( Figure 2, Table S1). 39 A specific frameshift mutation reported in this study (p.Ser2486Leufs*21) is located within the last exon and is therefore predicted to escape nonsense mediated decay (NMD) of the mutant mRNA transcript.…”
Section: Congenital Heart Diseasementioning
confidence: 99%
“…Truncating NOTCH1 mutations were identified in 2 families, members of whom presented with various aortic and cardiac anomalies, including BAV, CAVD, aortic stenosis, aortic insufficiency, TAA, Tetralogy of Fallot (TOF), ventricular septal defect (VSD), mitral atresia, hypoplastic left ventricle, and double‐outlet right ventricle (Figure ) . This initial report was followed by many others, describing an association between variations in NOTCH1 and BAV, BAV/TAA, hypoplastic left heart syndrome (HLHS), aortic valve stenosis, and coarctation . Most of the identified variants in these reports are missense variants, which do not replace or create critical cysteine or other conserved residues in the EGF‐like domains.…”
Section: Introductionmentioning
confidence: 99%